Saturday

April 19, 2014

April 19, 2014

Posted by **belinda** on Wednesday, March 3, 2010 at 11:48pm.

- math -
**drwls**, Thursday, March 4, 2010 at 5:53amTake out the common factor m. I am assuming the "n" is not part of the exponent.

3m^2* n + 2m = m*(3mn + 2)

**Related Questions**

math - factor (m/4 + n/3)(3m/4 - 2n/3) Is this the answer? if not, what did I do...

math - if 3M/2N=0.125, what is the value of N in terms of M? This is the workout...

math ALGEBRA - Solve by either the substitution method or the addition or ...

math - Solve each formula for n. 2n = 4xp-6 3m-n=4s r/n+2=p t=100(n+3) pv/nR=T ...

algebra - So... I know the answer to the question because it's something we ...

factoring - let f(m)=m^3 + 3m^2 + 3m + 1 notice f(-1) = 0, so m+1 is a factor. ...

algebra - Here is the problem I am working on and what I did so far: 4+m-3m ...

math - 31m^2n/41 x 21/mn x 2n^2/3m

Math - This irregular shape has 2m,2m,2m, 3m, 4m, 7m _2m_ _2m_ | |2m__3m_...

Math - Factor 1. a^4-16 2. (m-n)^2-(2m+3n)^2 3.2x^4y^4-6x^5y^3+8x^3y 4.12m^2n^3+...